Occluded vein as a predictor for complications in non-infectious transvenous lead extraction - Milman, Anat; Leshem, Eran; Massalha, Eias; Jia, Karen; Meitus, Amit; Kariv, Saar; Shafir, Yuval; Glikson, Michael; Luria, David; Sabbag, Avi; Beinart, Roy; Nof, Eyal (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiovascular implantable electronic device (CIED) use is steadily increasing, and complications include venous occlusion and fractured leads. Transvenous Lead Extraction (TLE) can facilitate re-implantation of new leads. Aims To explore predictors and complications of non-infectious TLE. Methods A retrospective analysis and comparison of characteristics, complications, and outcomes of patients with and without occluded veins (OV) undergoing TLE at our center. Results Eighty-eight patients underwent TLE for non-infectious reasons. Indications for TLE were lead malfunction (62; 70.5%) and need for CIED upgrade (22; 25%). Fourteen patients referred due to lead malfunction had an OV observed during venography. The OV group (36 patients) were significantly older (65.7±14.1 vs 53.8±15.9 respectively, p=0.001) and had more comorbidities. EF was significantly lower for the OV group (27.5% vs 57.5%, p=0.001) as was longer lead dwelling time (3226±2324 vs 2191±1355 days, respectively, p=0.012). Major complications were exclusive for the OV group (5.5% vs none, p=0.17), and most minor complications occurred in the OV group as well (33.3% vs 4.1% respectively, p<0.001). Laser sheath and Mechanical tools for TLE were frequently used for OV as compared to the non-occluded group (94.4% vs 73.5% respectively, p=0.012). Procedure success was higher in the non-occluded group compared to the OV group (98% vs 83.3%, respectively, p=0.047). Despite these results, peri-procedural mortality was similar between groups. Conclusions Among TLE for non-infectious reasons, vein occlusion appears as a major predictor for complex TLE tools use, complications, and procedural success. Venography should be considered prior to non-infectious TLE to identify high-risk patients.